Chemogenetic inhibition of amygdala excitatory neurons impairs rhEPO-enhanced contextual fear memory after TBI. (1st May 2023) - Celorrio, Marta; Friess, Stuart H.
Graphical abstract: Highlights: DREADDs-based chemogenetic usage in a murine model of TBI with delayed hypoxemia. Chemogenetic silencing of amygdala neurons impairs rhEPO behavioral improvements. rhEPO administration improves amygdala-dependent fear memory after TBI. Abstract: Erythropoietin (EPO) is a hypoxia-responsive cytokine that induces neuroprotective effect in hypoxic-ischaemic, traumatic, excitotoxic and inflammatory injuries. Recently, utilizing a clinically relevant murine model of TBI and delayed hypoxemia, we have found that ongoing recombinant human EPO (rhEPO) administration influenced neurogenesis, neuroprotection, synaptic density and, behavioral outcomes early after TBI, and the impact on long-lasting outcomes 6 months after injury. We also demonstrated that the 1-month behavioral improvement was associated with mitogen-activated protein kinase (MAPK)/cAMP response element-binding protein (CREB) signaling activation and increased of excitatory synaptic density in the amygdala. However, we did not uncover which type of cells were involved in fear memory response enhancement after rhEPO treatment in the setting of TBI with delayed hypoxemia. In this report, using chemogenetic tools in our controlled cortical impact (CCI) model, we were able to inactivate excitatory neurons and eliminate rhEPO-induced fear memory recall enhancement. In summary, these data demonstrate that rhEPO treatment initiated after TBI enhances contextual fear memory in the injured brain via activation of excitatory neurons in the amygdala.